Edukasi Keamanan Digital untuk Meningkatkan Literasi Digital Karyawan Perusahaan Daerah Sa-ijaan Mitra Lestari Kotabaru: Digital Security Education to Improve Digital Literacy Employees of the Regional Company Sa-ijaan Mitra Lestari Kotabaru - Ahyati, Inayatul Ulya; Pratiwi, Evi Lestari; Humaidi, Muhammad; Rozaq, Abdul (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Sa-ijaan Mitra Lestari (SML) Regional Company of Kotabaru Regency is a regionally-owned enterprise (BUMD) whose shares are 100% owned by the Kotabaru Regency Government. Until now, SML employees have never received outreach or training on digital literacy, especially concerning digital security. Therefore, this community service activity aims to raise their awareness and understanding of risks and threats in the digital world and teach best practices for protecting the company's information and systems. This Digital Security Education activity was carried out in five stages: preparation, implementation, evaluation, and report writing. The implementation phase was conducted through a seminar held at the SML office. The seminar was delivered using multimedia presentation slides containing text, images, and videos. Additionally, a Q&A session was included to ensure participants gained comprehensive knowledge. Evaluation results showed an increase in employees' awareness of cyber risks and preventive measures that can be taken. Employees became more aware of the importance of safeguarding the integrity of company data and information, and better prepared to face cyber threats. The success of this training also contributed to building a stronger digital security culture within the company, where every team member feels responsible for the security of the company's data.